Modelo de gestión contable y financiera para el sector hotelero en el Ecuador - Cajas Siguencia, Tamara Alexandra (2019)
For the present research work was "Accounting and financial management model for the hotel sector in Ecuador". Chapter 1 mentions the problems that exist in companies dedicated to the provision of hotel services, tourism and complementary services that allow them to maintain orderly information and in accordance with the regulations and legal provisions established by the control agencies. Application of accounting and financial processes that tourism companies lack has caused errors in the issuance of financial reports and therefore affect the disclosure of reliable economic results that facilitate their owners to make decisions efficiently, effectively and timely. Chapter 2 presents the referential theoretical framework that is made up of the conceptual and legal bases that sustain the investigated topic and its process. In Chapter 3 is the methodological framework that refers to the research methods and techniques used to collect, analyze and interpret the information to obtain the results. Chapter 4 describes the research proposal that is a model of accounting and financial management for the hotel sector, which has been prepared in accordance with procedures, accounting techniques and accounting principles……….